PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Sawal Sartono; Latifatul Isroiyah; Eldon, Mokhamad; Yohanna Adys Setyorini (Universitas Tulungagung, 2023)
This study aims to determine the direct effect of communication and motivation on employee performance as well as the indirect effect through job satisfaction used a causal associative method in quantitative approach. There were 40 samples collected. The data collection techniques used library research and field research, which then analysed through instrument testing, classical assumption testing, multiple regression analysis using path analysis, and goodness of fit testing. The variables used are communication (X1) and motivation (X2) as independent variables, while the dependent variable is employee performance (Y) and job satisfaction (Z) as intermediary or intervening variables.The results of this study are communication has a significant effect on employee performance, motivation has a significant effect on employee performance, communication has a significant effect on job satisfaction, motivation has a significant effect on job satisfaction, communication through job satisfaction has no significant effect on employee performance, and motivation through job satisfaction has no effect significant to employee performance.